Maternal socioeconomic position and psoriasis. (1st February 2019) - Groot, J.; Nybo Andersen, A.M.; Adam, A.; Tind Nielsen, T.E.; Blegvad, C.; Skov, L.
Summary: Psoriasis is a common skin disease that is often characterized by well‐defined red or scaly patches on the skin. The disease affects approximately 0.4 percent of children in Denmark, with similar rates in other western countries. Psoriasis occurring in childhood may be referred to as paediatric‐onset psoriasis. In this Danish study, the authors aimed to find out whether children with a lower socioeconomic position (from families with lower education, income and employment) were more likely to suffer from paediatric‐onset psoriasis compared to those with a higher socioeconomic position. The authors used data from a study in which mothers and their children participated from pregnancy and the children's birth until the children were 11 years old. At the 11‐year follow‐up of children, mothers were asked whether their child had psoriasis. Information on socioeconomic position was gathered by using data from official databases on the mothers' income, education and work. The authors investigated whether these factors affected the chances of their child developing paediatric‐onset psoriasis and found that they were strongly related. Children whose mothers had a lower education or income were more likely to have paediatric‐onset psoriasis than children whose mothers had a higher education or income. Social and economic circumstances at birth and in childhood appear to play a role in the risk of getting paediatric‐onset psoriasis.